Superficial Morphea: Clinicopathological Characteristics and a Novel Therapeutic Outcome to Excimer Light Therapy - Al-Sadat Mosbeh; Soha Aboeldahab; Mohamed El-Khalawany (Dermatology Research and Practice)
Introduction. Superficial morphea (SM) is an uncommon entity that was described in the literature without definitive correlation to localized scleroderma (LS) or other atrophoderma diseases. Aim. To demonstrate the clinicopathological features of SM and evaluate the efficacy of different therapeutic modalities in its management. Patients and methods. A total of 28 patients with SM were studied during the period from 2010 to 2015. Clinicopathological features and therapeutic outcomes were recorded and analyzed. Results. Clinically, SM was predominant in females (71.4%) with an average onset at 33 years of age and an average duration of 15 months. It was commonly presented as asymptomatic, darkly pigmented, and multiple and slightly indurated patches. The lesions were mostly ill-defined, large-sized, and located more on the trunk. Histologically, thickening of collagen fibers was observed either localized to the papillary dermis only (38.9%) or extended into the upper reticular dermis (61.1%). Elastic fibers were generally diminished in the upper reticular dermis while the number of fibroblasts and basal melanin pigmentation were increased in the majority of cases (92.9% and 96.4%, respectively). The most commonly associated diseases were diabetes mellitus (50%) and hepatitis C virus (HCV) infection (42.8%), and their incidence was significantly higher than that in patients with LS. Excimer light showed promising effective results in the treatment of most cases (78.9%) while the response to other modalities such as topical corticosteroid alone or in combination with tacrolimus or treatment with UVA1 alone was less effective (7.1%, 23.1%, and 5%, respectively). Conclusion. Our results proposed that SM is a distinctive clinicopathological variant and not a stage in the spectrum of LS. The novel response of SM to excimer light and not for UVA1 therapy also suggests the different therapeutic outcome of SM from LS. Although SM has a significant association with DM and HCV infection, they seem not to affect the course of the disease.